Finance and Development, December 1979. (Finance and Development; Finance and Development, 1979)
This paper highlights that the fight against worldwide inflation was the main theme of the Finance Ministers and central bank Governors from 138 member countries that participated in the 1979 Annual Meeting of the IMF's Board of Governors in Belgrade in October 1979. Unlike the agenda for the 1978 Meeting, which contained a number of single issues, such as quota increases and special drawing rights allocations, requiring specific decisions and action, the 1979 Meeting was devoted principally to a wide-ranging discussion of the world's economic problems.